Distribution and survival of leukemias in the mesoregion of the Potiguar West - Oliveira, Jéssica Costa; Torres, Taffarel Melo; Pereira, Wogelsanger Oliveira (Scientia Plena, 2018)
In the mesoregion of the Potiguar West, Rio Grande do Norte, Brazil, literature concerning distribution and survival rates of leukemia in the population is sparse. This study intends to perform this analysis, exploring epidemiological data on patients, up to 100 years old, diagnosed between 2005 and 2014. In total, 183 patients with any type of leukemia were considered; acute myeloid leukemia was the most frequent (66 cases). Male patients were predominant (59%) and most cases did not progress to death (59.1%). In relation to survival, patients with acute myeloid leukemia presented less survival of 10 years after diagnosis, while patients with chronic lymphoid leukemia were most survival rates. Thus, it was possible to better characterize leukemia in this region, which is critical to identify possible risk factors and establish priorities on prevention, planning, management and evaluation of health services.